Association of social support and mental health literacy with quality of life among university students during the Covid-19 pandemic - Musa, Siti Nur Syuhada; Hamzah, Siti Raba’ah; Badruldin, Muhammad Nur Waafi; Amiludin, Nurul Afifah; Zameram, Qurratul Ain; Kamaruzaman, Muhd Jamil Muhshi; Said, Nur Najwa; Ahmad Haniff, Nursyamimi Amirah (Human Resource Management Academic Research Society, 2022)
Social support is one of the main factors that influence the quality of one’s life. In this regard, mental health literacy is consistently associated with positive outcomes for students, in terms of their wellbeing and academic achievement. The present study is especially important to young people because understanding their quality of life can facilitate their life as a student and preparing them to their future of work. This study investigated the relationship between social support and mental health literacy in relation to the quality of life among Malaysian university students. A quantitative research paradigm was adopted, with a cross-sectional design using data collected from 140 randomly selected university students. The data was analyzed by SPSS software version 25 using the Pearson correlation and multiple linear regression. The results showed positive relationships between social support and mental health literacy towards quality of life. Thus, hypothesis 1 and hypothesis 2 was accepted. In the multiple linear analysis, nevertheless, mental health literacy was not found to influence the quality of life independently of social support. Appropriate programs should be designed and implemented to enhance the level of mental health literacy and, more importantly, to ensure adequate social support for students in order to promote a high quality of life.